Вычисление производной:f(x)=cosx-2sinx+3; f(x)=(5-2x)^6

0 голосов
66 просмотров

Вычисление производной:f(x)=cosx-2sinx+3;
f(x)=(5-2x)^6


Алгебра (15 баллов) | 66 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Для вычисления данных производных нужно знать несколько формул:
1)
 (f(x)+g(x))'=f'(x)+g'(x)
2) 
(Cf(x))'=Cf'(x),\, C=const
3) 
(f(g(x)))'=g'(x)*f'(g(x))
4) 
(\cos(x))=-\sin(x),\,(\sin(x))'=\cos(x),\,(C)'=0\,\, (C=const),\\(x^n)'=n*x^{n-1}

Вычисляем:

(\cos x-2\sin x+3)'=(\cos x)'-2(\sin x)'+(3)'=-\sin x-2\cos x

((5-2x)^6)'=(5-2x)'*(6(5-2x)^5)=-12(5-2x)^5=12(2x-5)^5

(18.9k баллов)